2016
DOI: 10.1109/tuffc.2016.2551705
|View full text |Cite
|
Sign up to set email alerts
|

High-Frame-Rate Synthetic Aperture Ultrasound Imaging Using Mismatched Coded Excitation Waveform Engineering: A Feasibility Study

Abstract: Mismatched coded excitation (CE) can be employed to increase the frame rate of synthetic aperture ultrasound imaging. The high autocorrelation and low cross correlation (CC) of transmitted signals enables the identification and separation of signal sources at the receiver. Thus, the method provides B-mode imaging with simultaneous transmission from several elements and capability of spatial decoding of the transmitted signals, which makes the imaging process equivalent to consecutive transmissions. Each transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Bahman Lashkari et al studied the use of mismatched encoded excitation, which involves using excitation signals with high autocorrelation and low cross-correlation, to identify and separate signal sources at the receiver, enabling transmission from multiple elements simultaneously and allowing for the spatial decoding of transmitted signals [81]. This approach makes the imaging process equivalent to continuous transmission, greatly improving the efficiency of phased array synthetic aperture imaging.…”
Section: Multi-beam Parallel Transmission High Frame Rate Imaging Det...mentioning
confidence: 99%
See 1 more Smart Citation
“…Bahman Lashkari et al studied the use of mismatched encoded excitation, which involves using excitation signals with high autocorrelation and low cross-correlation, to identify and separate signal sources at the receiver, enabling transmission from multiple elements simultaneously and allowing for the spatial decoding of transmitted signals [81]. This approach makes the imaging process equivalent to continuous transmission, greatly improving the efficiency of phased array synthetic aperture imaging.…”
Section: Multi-beam Parallel Transmission High Frame Rate Imaging Det...mentioning
confidence: 99%
“…The most commonly used coded excitation signal is the LFM signal. Multiple LFM signals can be generated by changing their parameters, achieving a mismatched effect with high autocorrelation and low cross-correlation [81][82][83]. The most common approach is to keep the bandwidth and duration of the LFM signal unchanged while varying the sweep rate, i.e., sweeping through the same frequency range at different rates.…”
mentioning
confidence: 99%
“…It should be added that the use of mismatched coded excitations is not limited to two codes. It has been shown that it is possible to generate multiple mismatched coded excitation signals with identical bandwidth and code length [16]. Thus, while sharing the same signal (image) resolution, each wavelength generates its own PA response.…”
mentioning
confidence: 99%